2014
DOI: 10.4414/smw.2014.13982
|View full text |Cite
|
Sign up to set email alerts
|

Admissions of patients with alcohol intoxication in the Emergency Department: a growing phenomenon

Abstract: We observed an increase in the percentage of admissions with positive BAC that was not limited to younger individuals. Given the potential consequences of alcohol intoxication, and the large burden imposed on ED teams, communities should be encouraged to take measures aimed at reducing alcohol intoxication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…From a previous study, we know that in 2006, 6.5% of all admissions had a BAC test, and that 73% of those tests were positive. In 2007, 7.6% of all admissions had a BAC test, and 74% of those tests were positive (Bertholet et al, 2014). If patients were admitted for alcohol intoxication more than once during the target period, only the first admission was considered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a previous study, we know that in 2006, 6.5% of all admissions had a BAC test, and that 73% of those tests were positive. In 2007, 7.6% of all admissions had a BAC test, and 74% of those tests were positive (Bertholet et al, 2014). If patients were admitted for alcohol intoxication more than once during the target period, only the first admission was considered.…”
Section: Methodsmentioning
confidence: 99%
“…According to the 2011 World Health Organization global status report on alcohol and health, alcohol use is a leading cause of mortality in young adults (WHO, 2011). Alcohol use also leads to numerous hospital admissions in young adults (WHO, 2011;Shield et al, 2012), including in Switzerland (Bertholet et al, 2014). In recent years, several studies conducted in Switzerland and in France have shown increases in alcohol intoxication admissions, especially for those aged 16-25 (Haberkern et al, 2010;Menecier et al, 2012;Bertholet et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We did not observe a significant increase in adolescents, which is not consistent with global trends. This could implicate that the global trend of more young alcohol intoxicated patients presenting at the ED is demographic dependent although this should first be confirmed by further investigation [7,11,12]. Since alcohol consumption decreased by 18% over the last 20 years in Belgium, but total number of ED visits due to alcohol intoxication increased, we can assume that there has been a change in alcohol consumption pattern [8,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Na slične rezultate nailazimo u Godišnjaku Nacionalnog centra za kontrolu trovanja za 2014. godinu u Srbiji, u kome se navodi da su u najvećem procentu (51,00%) ambulantno zbrinuti pacijenti zbog toksičnih efekata alkohola (3). Studija u Lozani, Švajcarska, u ispitivanom periodu od 2002. do 2011. godine, zabeležila je da je od ukupnog broja hospitalizovanih, čak 72% pacijenata imalo pozitivnu koncentraciju alkohola u krvi, što pokazuje veliku prisutnost hospitalizovanih zbog akutne alkoholne intoksikacije širom Evrope (13). Studije su pokazale da su lekovi bili najčešći uzrok akutne intoksikacije i u Zagrebu, Hrvatska (14).…”
Section: Rezultatiunclassified
“…Utvrđeno je da je najveći broj intoksikovanih imao koncentracije alkohola u krvi između 1,5 i 3,0‰ (39,84%), sa prosečnom koncentracijom 2,23 (± 0,42) promila. Na slične rezultate su naišli i u studiji u Švajcarskoj, gde je prosečna koncentracija alkohola u krvi tokom desetogodišnjeg perioda iznosila 2,12 ± 1,4‰ (13).…”
Section: Rezultatiunclassified